The labor market and its effect on the economy - Abdiyeva, Nilufar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The purpose of the article is to determine the nature and connection of the labor market with entrepreneurship and business. The tools of labor market policy used in economic practice are presented, which makes it possible to understand its operation and impact on the economy as a whole. The article identifies practical tools in the labor market and strategies that directly affect the activity of economic organizations and the state economy as a whole.